Commentary: Should the Belmont Report Be Extended to Animal Research - AGUILERA, BERNARDO; WENDLER, DAVID (Cambridge quarterly of healthcare ethics, 2020)
In “A Belmont Report for Animals?” Hope Ferdowsian, et al. offer an important contribution to the burgeoning literature on animal ethics, focusing on the complex issue of animal research regulation. As the authors note, current animal regulatory schemes and guidelines have important gaps and inconsistencies, while the most influential framework, the ‘three Rs,’ (i.e., Replacement, Refinement, and Reduction) is outdated and has fallen behind growing public concern regarding the appropriate treatment of animals. Perhaps the primary flaw in current animal research regulation, they argue, is the “general assumption that, when in conflict, human interests outweigh animal interests,” thus giving researchers leeway to justify the use of animals in a broad range of burdensome and painful experiments, including experiments that offer little benefit to human beings.In the authors’ view, this assumption ignores the fact that animals and human beings have equal moral status, in the sense that “animal interests should be given approximately equal moral weight as human interests.” The authors then consider how the regulations for animal research need to be revised to be consistent with this view. They propose to extend the influential principles for human research formulated in the Belmont Report, viz., respect for persons, beneficence and justice, to cover research with animals. Based on this approach, they argue for three important claims: (1) harms to animals should be weighted equivalently to relevantly similar harms to humans, leading to similar protections, (2) animals should be considered vulnerable to the extent that it is unfair to use them for research that does not offer potential net-benefit to them, and thus (3) animals’ enrollment in research should generally be avoided.The authors’ analysis leads to a largely abolitionist view of research involving animals, at least as we know it. More precisely, they claim that consistent extrapolation of the Belmont Report points to a regulatory scheme that restricts research to nondissenting household animals diagnosed with a condition or disease, enrolled in studies that offer net-benefit, and based on the permission of an appropriate surrogate decisionmaker.